Adsorption of Tofu Liquid Waste Using Rice Husk Activated Carbon - Daning Kinanti Sutama; Alfiana, Aulia Firda; Rizkita, Nadya; Indah Lestari, Dwi; Aminah, Siti (Science Education and Application Journal, 2025)
Adsorption of Tofu Liquid Waste Using Rice Husk Activated Carbon. Rice husk is an agricultural by-product rich in organic matter, and improper management can cause environmental pollution. Given the high carbon content in rice husk, it can be used as an adsorbent. Furthermore, the type of activator and activation technique employed impact the properties of activated carbon. Due to its ability to produce activated carbon with a high pore volume and specific surface area, KOH is a chemical substance that is frequently employed. This study sought to ascertain whether rice husks might be used as activated carbon to lower the amount of organic matter in liquid effluent from the tofu business. The results of this study indicate that rice husk activated carbon can reduce the level of TDS by 27%, TSS by 97%, and pH 6 from the initial level. The optimum contact time is 120 minutes at a ratio variation of 1:130, because at that time the activated carbon has approached saturation by the adsorbed adsorbate and experienced equilibrium and saturation.